IL‐10 derived from M2 macrophage promotes cancer stemness via JAK1/STAT1/NF‐κB/Notch1 pathway in non‐small cell lung cancer. Issue 4 (7th February 2019) - Yang, Li; Dong, Ying; Li, Yanjun; Wang, Dong; Liu, Shasha; Wang, Dan; Gao, Qun; Ji, Shaofei; Chen, Xinfeng; Lei, Qingyang; Jiang, Wenyi; Wang, Liping; et al.
Abstract : Tumor‐associated macrophages (TAMs), key immune cells in the tumor microenvironment, are shown to be closely correlated with the progression of non‐small cell lung cancer (NSCLC). Cancer stem cells (CSCs) can contribute to NSCLC progression as well. We aimed to clarify whether TAMs promote the progression of NSCLC by mainly affecting the activities of CSCs. We found that TAM‐like cells promoted CSC‐like properties in NSCLC cells in vitro, which was mediated by TAM‐derived IL‐10. TAM‐derived IL‐10 promoted CSC‐like properties of NSCLC cells through JAK1/STAT1/NF‐κB/Notch1 signaling. Blockade of IL‐10/JAK1 signaling inhibited TAM‐mediated NSCLC tumor growth in vivo, and the TAM‐mediated expression of CSC‐related and mesenchymal‐related genes in NSCLC. Lastly, expression levels of these signaling molecules were significantly correlated with survival of NSCLC patients. Therefore, IL‐10/JAK1 signaling might be a potential therapeutic target for NSCLC treatment. Abstract : What's new? The plasticity of cancer stem cells (CSCs) may be regulated by factors in the tumor microenvironment; underlying mechanisms however remain unclear in non‐small cell lung cancer (NSCLC). Here, the authors find that IL‐10 is highly expressed in NSCLC tumor‐associated macrophages (TAMs). TAM‐secreted IL‐10 promotes CSC‐like properties and tumor growth in NSCLC via JAK1/STAT1/NF‐κB/Notch1 signaling. Blockade of this signaling through shRNA IL‐10RA A549 cells and JAK1 inhibitor biricitinib inhibits TAM‐induced activity of CSCs. High expression levels of the reported signaling molecules are closely correlated with poor patient prognosis. The findings highlight IL‐10/JAK1 signaling as a potential therapeutic target for NSCLC treatment.